A Meta-Study of Publication Patterns for the Rehabilitation Counseling Bulletin From 2001 to 2012. (October 2014) - Lenz, A. Stephen; Darnell, April; Fitzgerald, Lacey; Brownlee, Tera
We conducted a meta-study of research articles published in Rehabilitation Counseling Bulletin from 2001 to 2012. Variables associated with authors (biological sex, setting, domicile) and study characteristics (sample and research methodology) were coded and analyzed across groups of 4-year publication periods. Our findings and related implications for the rehabilitation counseling profession are discussed.